2006
DOI: 10.1063/1.2400034
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of water adsorption at reduced and stoichiometric ceria (111) surfaces

Abstract: We study the structure and energetics of water molecules adsorbed at ceria (111) surfaces for 0.5 and 1.0 ML coverages using density functional theory. The results of this study provide a theoretical framework for interpreting recent experimental results on the redox properties of water at ceria (111) surfaces. In particular, we have computed the structure and energetics of various absorption geometries at the stoichiometric ceria (111) surface. We find that single hydrogen bonds between the water and the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
88
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 37 publications
18
88
1
1
Order By: Relevance
“…This suggests that the (111) surface does not exhibit a strong driving force to bind hydroxide species to surface sites. These results compared favourably to the results of Kumar and Schelling [28]. In particular, we calculated a hydroxylation energy of 0.55 eV for the (111) surface at 50% hydroxylation, while Kumar and Schelling calculated adsorption energies of 0.56 and 0.58 eV for two different configurations of a 0.5 monolayer of water on the (111) surface.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This suggests that the (111) surface does not exhibit a strong driving force to bind hydroxide species to surface sites. These results compared favourably to the results of Kumar and Schelling [28]. In particular, we calculated a hydroxylation energy of 0.55 eV for the (111) surface at 50% hydroxylation, while Kumar and Schelling calculated adsorption energies of 0.56 and 0.58 eV for two different configurations of a 0.5 monolayer of water on the (111) surface.…”
Section: Resultssupporting
confidence: 68%
“…Similarly, Abramowski et al [26] and Tan et al [27] simulated the hydroxylation behavior of UO 2 and PuO 2 , respectively, and again predicted that the crystallite morphology of these compounds is different in the presence of water. Finally, Kumar and Schelling recently considered the adsorption of water on the CeO 2 (111) surface via density functional theory [28]. We will compare our results to those of Kumar and Schelling in the ''Results'' section.…”
Section: Previous Ceo 2 Surface Simulation Studiesmentioning
confidence: 73%
“…27͒ and other reported theoretical results. 14,28 The nonpolar CeO 2 ͑111͒ surface, the structurally most close-packed, is found to be the energetically most stable surface. Gennard et al 29 have shown that a slab containing nine CeO 2 ͑111͒ layers is sufficient to converge the important surface properties including surface energy, Mulliken charges and electron densities.…”
Section: A Computational Methodsmentioning
confidence: 97%
“…Numerous approaches based on DFT theory, ranging from LDA [20] to GGA [21] and DFT + U [8,19], have been employed to investigate cerium oxides. The LDA or GGA methods are considered unable to describe the electronic structure of CeO 2 in the presence of oxygen vacancies because of the excess electrons (4f) induced by the creation of oxygen vacancies, which can occupy the strongly localized f orbital.…”
Section: Methods Selectionmentioning
confidence: 99%